The influence of seed size and seed pre-treatment on germination, early seedling growth, field survival and growth of Pinus elliottii - Chirwa, Paxie W. (University of Pretoria, 2022)
Dissertation (MSc (Forestry Science))--University of Pretoria, 2022.